UJI EFIKASI INSEKTISIDA BAHAN AKTIF PERMETRIN 300 g/l TERHADAP POPULASI HAMA ULAT DAUN (Plutella xylostella L) PADA TANAMAN KUBIS (Brassica oleracea) - JOKO KUSNANTO; TYAS SOEMARAH KURNIA DEWI; AGUS BUDIYONO; ENDANG SUPRAPTI; HARYUNI HARYUNI (JURNAL ILMIAH AGRINECA, 2019)
Cabbage plants (Brassica oleracea) are one of the vegetables that are widely cultivated by farmers in Indonesia, both in the highlands and lowlands. Cabbage plants are usually cultivated at the beginning of the dry season. Cabbage has high production potential and its marketing is relatively easy. So that it is right if the cabbage is prioritized as one of the leaf vegetable plants that needs to be further developed. Cabbage production in the last six years shows a trend of fluctuations every year. Production in 2012 increased by 0.14% to 7,550,021 tons from 7,539,533 tons, then increased by 1.95% to 7,469,013 tons in 2013, and decreased 3.06% to 7,461,697 tons in 2014, then in 2015 it decreased 2.62% to 7,265,840 tons, then in 2016 the production increased to 7,274,126 tons and subsequently in 2017 it increased 2.64%. Fluctuations in cabbage production are inseparable from the effect of an increase or decrease in the area of harvest and the attack of plant pests. The aim of this study was to determine the most effective concentration of the active ingredient of Permethrin 300 g/l to control Plutella xylostella L caterpillar pest in cabbage plants. This research was conducted in Sudimoro Village, Teras Subdistrict, Boyolali Regency at an altitude of 196 m above sea level with alluvial brown soil types, with soil solum thickness > 90 cm. Based on the Oldeman classification, Sudimoro Village is a D3 zone, with a wet month length of 3-4 months and a dry month length of 3-6 months. The method used in the study was a non factorial Complete Group Randomized Design (RAKL) with 5 (five) different concentrations of insecticide treatments. The concentration treatments used were 1 cc/ liters (C1), 0.75 cc/ liters (C2), 0.5 cc/ liters (C3), 0.25 cc/ liters (C4), and control (C5). The results showed that the treatment of the active ingredient concentration of insecticide Permethrin 300 g/l had a very significant effect on the parameters of the Plutella xylostella L population, the weight of the wet stover, the weight of the crop, and the diameter of the crop. However, it does not significantly affect the parameters of plant height and dry stover weight.The effectiveness of the active ingredient insecticide Permethrin 300 g/l in the parameters of the population of Plutella xylostella L is best in the treatment concentration of 0.75 cc/ liters (C2), with a 100% efficacy rate.